Rise up, o judge : a study of justice in the biblical world - Nardoni, Enrique, 1924-2002. (Peabody, Mass. : Hendrickson Publishers, 2004)
"Rise Up, O Judge studies the biblical concept of social and liberating justice and traces its roots to the cultures of ancient Mesopotamia and Egypt. The application of justice through its developing stages within the various environments and communities of the Old and New Testaments is then analyzed. Enrique Nardoni reads the ancient and biblical texts in their own historical, social, and intellectual context, but he also relates them to contemporary culture, where his readers are participants, not mere spectators. Translated for the first time into English, this ground-breaking work will serve as an outstanding resource for teaching and discussing the issue of social justice in universities, seminaries, and religious communities."--BOOK JACKET.
Ch. 1. Justice in ancient Mesopotamia -- Ch. 2. Justice in ancient Egypt -- Ch. 3. Exodus as an event of liberating justice -- Ch. 4. Norms of justice in the laws of the covenant -- Ch. 5. Justice, monarchy, and prophecy -- Ch. 6. Justice in the Psalms and wisdom books -- Ch. 7. Justice in apocalyptic writings -- Ch. 8. Justice in the ministry of Jesus of Nazareth -- Ch. 9. Justice in the gospel of Mark -- Ch. 10. Justice in the gospel of Matthew and the letter of James -- Ch. 11. Justice in the gospel of Luke and the acts of the apostles -- Ch. 12. Justice in Paul's letters -- Ch. 13. Justice in the Johannine writings -- Ch. 14. Overall conclusion.
Includes bibliographical references and indexes.
Keywords: Justice -- Biblical teaching